Architecture and Impact of an Open, Online, Remixable, and Multimedia-Rich Algebra 1 Course - Bissell, Ahrash N (Online Learning, 2012)
The question we face is whether technology in general, and OER in particular, might offer some solutions for improving math scores across the nation.